MANAJEMEN SUMBERDAYA KELUARGA: SUATU ANALISIS GENDER DALAM KEHIDUPAN KELUARGA NELAYAN DI PESISIR BONTANG KUALA, KALIMANTAN TIMUR - Qoriah Saleha; Hartoyo Hartoyo; Dwi Hastuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2008)
The earning and work of fisherman families in Indonesia mostly depend on natural resources using only simple technology. The study was conducted in coastal area of Bontang Kuala, East Kalimantan Province in June and July 2002. One most densely populated sub district was chosen purposively. Result showed that the average income of its family per capita was higher than the average of Indonesian family. Family decision making in economic activities such as fishing investment, catchment’s area selection, technology application were dominated by husband, while in religious, health and domestic activities except child education were dominated by wife. Higher the average contribution of wives to family income the higher the domination of wives in decision making in all activities that commonly dominated by husband. Time allocated for domestic, social, health, and economic activities of wife were higher than that of husband, while for income earning activities husbands’ time was higher that of wives’. Correlation between variables showed that there was significant correlation between public decision making with public division of labor, and level of satisfaction of wives concerning public decision making but not with domestic decision making. Among domestic division of labor there were negative correlation with productive time and with leisure time of wives but not with public division of labor, and husbands’ time allocation.